Health Literacy and Outcomes among Patients with Heart Failure - Peterson, Pamela N (JAMA, 2011)
CONTEXT: Little is known about the impact of low health literacy among patients with heart failure (HF), a condition that requires self-management and frequent interactions with the healthcare system. OBJECTIVE: Evaluate the association between low health literacy and all-cause rehospitalization and mortality among outpatients with HF. DESIGN AND SETTING: Retrospective cohort study performed at Kaiser Permanente Colorado, an integrated managed care organization. Patients with HF were identified between Jan, 2001 and May, 2008 and followed for a mean of 1.2 years. Patients were surveyed. Health literacy was assessed using three established screening questions and categorized as adequate or low. PATIENTS: Outpatients with HF. MAIN OUTCOMES: All-cause mortality and hospitalization. RESULTS: The survey response rate was 72%. Of 1494 patients, 262 (17.5%) had low health literacy. Patients with low health literacy were older, of lower socioeconomic status, less likely to have at least a high school education and had higher rates of coexisting illnesses. In multivariable Cox regression, low health literacy was independently associated with higher mortality (unadjusted 17.6% vs. 6.3%; adjusted hazard ratio [HR]: 1.61; 95% CI 1.06–2.43; p=0.026), but not hospitalization (30.5% vs. 23.2%; HR:1.04; 95% CI 0.79–1.37; p=0.760). CONCLUSIONS: Among patients with HF in an integrated managed care organization, low health literacy was significantly associated with higher all-cause mortality.